Perceptions of Preventive Health Care and Healthy Lifestyle Choices for Low Income Families: A Qualitative Study. (3rd April 2013) - Fleary, Sasha A.; Ettienne-Gittens, Reynolette; Heffer, Robert W.
Abstract : This paper examines Head Start parents' perceptions of preventive health and healthy lifestyle choices and Head Start administrators' perceptions of the needs of parents they serve. To address the preventive health of the population, it is necessary that we explore perceptions, risks, and protective factors of preventive health. Focus groups were conducted with parents and administrators to elicit this information and to obtain suggestions for improving preventive health and healthy lifestyle choices among this group. Overall, nutrition and physical activity emerged as themes in parents' definition of preventive health and healthy lifestyle choices. They further identified social support and education as major protective factors for engaging in preventive health and healthy lifestyle choices. Results of this study can be used to inform research and practice to develop interventions to increase preventive health and healthy lifestyle choices among low income families.